SOURCES OF RARE METALS IN PERALUMINOUS GRANITES: A REVIEW OF GEOCHEMICAL AND ISOTOPIC DATA - Kostitsyn Yu.A. (My University, 2001)
A review is presented on published geochemical and isotopic (Sm-Nd and Rb-Sr) data on the worldwide occurrence of rare-metal granites and greisens in comparison with barren granites of the I and S types. The ratios of major and minor components in these granitoids suggest that high-P rare-metal granites resulted from the evolution of granitic melt of the S type, whereas low-P varieties were produced by I-type melts. Low-P granitic melts evolve mainly by means of crystallization differentiation, and the evolution of high-P rare-metal granites seems to have additionally involved the redistribution of elements by late magmatic fluids. The possibility of the origin of rare-metal melt does not depend on the type of source material from which the melt was derived (whether these were predominantly sedimentary or magmatic rocks). The geochemical and isotopic signatures of rare-metal granites testify that their sources could not be rocks notably enriched or depleted in rare elements and F compared with the sources of common granites. Neither could rare-metal melts be derived by the preferable mobilization of the micaceous constituent of the source. The enrichment of F and rare metals most probably resulted from the fractional crystallization of normal granitic melts of the I and S types. High-Al rare-metal granites worldwide show a much narrower ranges of isotopic variations (their εNdT ranges from -6.0 to +1.4) than those of normal granitoids (εNd from -19 to +8), which may be explained by the melting of crustal silicate rocks under the effect of intrusions of deep-seated mafic melts, from which the acid melts received energy required for their further evolution. The exchange in heat and material is reflected in the Nd isotopic signatures of rare-metal granites.